Helicobacter pylori is undetectable in intraductal papillary mucinous neoplasm - ÇELİKEL, ÇİĞDEM; BAĞCI ÇULÇİ, PELİN (ELSEVIER SCIENCE BV, 2016)
Background: About half of the world population is infected with Helicobacter pylori (H. pylori), a bacterium associated with gastric cancer and considered to be a risk factor for pancreatic ductal adenocarcinoma. Whether the bacterium is associated with intraductal papillary mucinous neoplasm, believed to be a precursor of pancreatic ductal adenocarcinoma, is unknown. The aim of this study was to investigate the presence of H. pylori DNA in tissue sections of intraductal papillary mucinous neoplasm. Methods: The presence of H. pylori DNA was tested in a retrospective controlled study of formalin-fixed, paraffin-embedded pancreatic tissues from 24 patients who underwent surgery for intraductal papillary mucinous neoplasm. Histologically normal tissues surrounding neoplasms were used as control. H. pylori DNA was evaluated after deparaffinization, DNA extraction, and purification, and results were evaluated statistically. Results: Samples were collected from 13 males and 11 females with mean age 59 years (range 44-77), and consisted of 19 cases of main-duct and three cases of branched-duct intraductal papillary mucinous neoplasm. Two patients were diagnosed with pancreatic cancer and main-duct intraductal papillary mucinous neoplasm. H. pylori DNA was not detected either in intraductal papillary mucinous neoplasm tissue, or in surrounding normal tissue. Conclusions: Although H. pylori has been implicated in pancreatic ductal adenocarcinoma, it may not play a key role in the development of intraductal papillary mucinous neoplasm. (C) 2016 IAP and EPC. Published by Elsevier B.V. All rights reserved.
Keywords: Hpylori; Intraductal papillary mucinous neoplasm; Pancreatic ductal adenocarcinoma; INDUCED ACUTE-PANCREATITIS; PARAFFIN-EMBEDDED TISSUES; POLYMERASE-CHAIN-REACTION; AUTOIMMUNE PANCREATITIS; CYSTIC NEOPLASMS; DNA EXTRACTION; INFECTION; CANCER; RISK; CARCINOMA